THE INFLUENCE OF LEARNING MOTIVATION AND INTEREST ON STUDENTS’ LEARNING OUTCOMES - Megawati; Gusmita, Emilya; Emelinda (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This research aims to see the influence of student learning and interest in statistics courses on student achievement at STIA Nusantara Sakti Sungai Penuh students. The research approach used is a quantitative approach. The sample in this study consisted of 30 people who were first semester students of the 2024 academic year who took statistics courses. The data collection tool used is a questionnaire/questionnaire which contains a set of statements that must be selected by respondents in the form of a Likert scale. The analysis tool uses multiple linear regression analysis. Hypothesis testing uses the F test and t test. Data processing was carried out using SPSS version 25. The results of the study showed 1) There is a significant influence of learning motivation and interest in statistics courses on the learning achievement of STIA Nusantara Sakti Sungai Penuh students simultaneously and partially, 2) There is a large influence of learning motivation and interest on the learning achievement of STIA Nusantara Sakti Sungai Penuh students as a whole. Simultaneous is 79% and the remaining 21% is influenced by other variables not studied. The partial influence is that motivation influences learning achievement by 54.21% and interest influences learning achievement by 24.77%, 3) The variable that most influences achievement learning is motivation namely 54.21%. Keywords: learning motivation, interest, learning achievement, multiple linear regression analysis